CONSTRUCTIVISM AND INTIGRATION OF ICT: POWERFUL BLEND OF TEACHING – LEARNING PROCESS - Shukla, Ashka (PEOPLE: International Journal of Social Sciences, 2015)
Constructivism states that learning takes place in contexts, while technology refers to the designs and environments that engage learners. This study was based on two premises. The first concerns the implementation of the ICT-enhanced constructivist learning today in classroom. The second refers to the emerging need for the appropriate teacher education and professional development as a presupposition for the implementation of constructivist innovation in classrooms.